2010
DOI: 10.1002/syn.20861
|View full text |Cite
|
Sign up to set email alerts
|

Neuron‐glial cell communication in the traumatic stress‐induced immunomodulation

Abstract: We have previously reported that neuron and glia could collaboratively govern the immunomodulation in traumatic rats. Herein, we characterized the sequential involvement of cortical neuron, microglia, and astrocytes in the traumatic stress-mediated neuroimmune modulation. At day 1 of trauma, transient extracellular signal related kinase 1/2 (ERK1/2) activation was initiated in neuron and microglia, which was accompanied by RSK-1 expression in the cytosol. At day 3 of trauma, persistent ERK1/2 activation occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Ultimately, reductions in synaptic numbers and the amplitude of the field excitatory postsynaptic potential (EPSP) happened during the aging [31]. In the present study, we demonstrated that synaptic Fyn activity was greatly augmented at day 3after trauma, with higher magnitude in 1-year mice that that in 2-month counterpart, together with our previous observation, namely, discordant Fyn signaling events was responsible for the deteriorated immuno-suppression and prolonged recovery aged rats during the traumatic stress [8,32], then, the result reinforced the idea that Fyn signaling might actively communicate with pre and post-synaptic elements of neuronal terminals influencing stress like events.…”
Section: Discussionsupporting
confidence: 72%
“…Ultimately, reductions in synaptic numbers and the amplitude of the field excitatory postsynaptic potential (EPSP) happened during the aging [31]. In the present study, we demonstrated that synaptic Fyn activity was greatly augmented at day 3after trauma, with higher magnitude in 1-year mice that that in 2-month counterpart, together with our previous observation, namely, discordant Fyn signaling events was responsible for the deteriorated immuno-suppression and prolonged recovery aged rats during the traumatic stress [8,32], then, the result reinforced the idea that Fyn signaling might actively communicate with pre and post-synaptic elements of neuronal terminals influencing stress like events.…”
Section: Discussionsupporting
confidence: 72%
“…Microglia are directly activated when exposed to B. burgdorferi and involved in neuronal-glia and glial communication [32]. While multiple cell types in the brain express MHC, in studies using minocycline (a suppressor of microglia) microglia activation was essential to induce stress-induced ERK1/2 neuroimmune modulation [33]. Further, the rapid increase in the expression of IL-1 receptor on microglia in response to endotoxin and vascular occlusion support the role of microglia as being a primary initiator of the neuroimmune response [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…RSK2 is as well implicated in cellular functions (10,11,15,23,36,52) and tumorigenesis (12,33). Although RSK is known to be regulated at the posttranscriptional level by phosphorylation (12,36), it has also been shown that the expression of RSK protein in the frontal cortex is enhanced by hypoxic preconditioning (44) or traumatic stress (54). In this work, we found that daily stress exposure induced dorsal horn RSK2 expression in the dorsal horn of rats.…”
Section: Discussionmentioning
confidence: 54%